Sistem Peramalan Kebutuhan Hidup Layak Minimum (Kapita/Bulan) Kota Bandung - Fahrudin, Rifqi; Sumitra, Irfan Dwiguna (Universitas Diponegoro, 2019)
The importance of inflation forecasting is used as a reference for estimating the Need for Living (KHL). If inflation can be predicted with high accuracy, it can certainly be used as the basis for government policy making in anticipating future economic activity. This study aims to produce a model of inflation data forecasting system, the forecasting results can be used as a reference for determining the Decent Living Needs (KHL) of a single worker in one month. The data used in forecasting is inflation data for January 2011 - December 2017 while the KHL data for the food and beverage category is obtained from the food price portal. The method used in this study is the SARIMA-SES hybrid method. In forecasting the inflation rate where the data is in the form of time series, the SARIMA-SES hybrid method can show more accurate forecasting results than using a single method. Based on the comparison of the overall forecasting model and by combining the SARIMA (1,0,1) (1,0,1) 12 and SES models with alpha 0,6 the smallest error value with MAD value 0,114, MSE 0,017 and 0,39% for MAPE. From these results, it was gathered that inflation forecasting in Bandung City using the SARIMA-SES hybrid method has a high accuracy value so that the results of the KHL value calculation with the forecasting inflation value approach the actual value. From these values can be used as a reference for the decision making of a single worker in fulfilling their life needs one month.